Analysis of the Influence of Social Media Influencers and Sharia Investment Galleries on the Investment Interest of Sharia Economics Students in the Capital Market - Ashlihah, Ashlihah; Darajat Mahmudi; Mei Santi; Rokhmat Subagiyo; Agus Eko Sujianto (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2026)
Introduction: Investment interest in the sharia capital market among Islamic economics students is an important aspect of strengthening Islamic financial inclusion. In the digital era, social media influencers are considered capable of shaping students’ perceptions and financial decisions, while Islamic investment galleries function as educational facilities that introduce sharia capital market instruments. This study aims to analyze the influence of social media influencers and Islamic investment galleries on the investment interest of Islamic economics students at KH. A. Wahab Hasbullah University Tambakberas Jombang. Methods: This study employed a quantitative approach with a survey method involving 65 active students selected as respondents. Data were collected through a Likert-scale questionnaire distributed via Google Forms and analyzed using multiple linear regression with the assistance of SPSS 26. Hypothesis testing was conducted through instrument tests, classical assumption tests, t-tests, and F-tests. Results: The findings indicate that partially, social media influencers have a positive and significant effect on students’ investment interest, and Islamic investment galleries also have a positive and significant effect. Simultaneously, both variables significantly influence students’ investment interest in the capital market. Conclusion and suggestion: Social media influencers and Islamic investment galleries are important factors in increasing students’ investment interest. Therefore, optimizing digital financial literacy through credible influencers and strengthening the role of Islamic investment galleries as educational and practical investment laboratories are recommended to enhance students’ participation in the sharia capital market.